THE CONSUMER CONFIDENCE REPORT – A TOOL FOR DEVELOPING MARKETING STRATEGIES DESIGNED FOR THE ONLINE ENVIRONMENT - Fuciu, Mircea; Dumitrescu, Luigi (Annales Universitatis Apulensis Series Oeconomica; Vol 2 No 19 (2017): Annales Universitatis Apulensis Series Oeconomica, 2017)
The consumers are the backbone of all marketing strategies, decisions and actions, but at the same time, it has become extremely important to gain and keep the consumers happy and close to your company, brand or product. Our paper aims to present an important marketing tools that the companies and their management teams can use to develop marketing strategies designed for the online environment of the 21st Century: the consumer confidence report. We are presenting the main tools developed for creating such a report: Consumer Confidence Index (CCI) and The Michigan Consumer Sentiment Index (MCSI), their advantages and disadvantages. We will present the manner in which we can use the consumer confidence report to develop new marketing strategies for the next period of time. The paper also underlines a statistical analysis of the consumer confidence reports for eastern and south-eastern European countries for the 2010 – 2016 timeframe. We point out the main reasons for the differences between the figures and these countries considering their demographical profile.